2018
DOI: 10.1053/j.jfas.2017.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clamp Reduction and Manual Reduction of Syndesmosis in Rotational Ankle Fractures: A Prospective Randomized Trial

Abstract: An optimal outcome of surgical treatment for a syndesmotic injury depends on accurate reduction and adequate fixation. It has been suggested that the use of a reduction clamp for reduction of the syndesmosis results in better reduction and a lower rate of redisplacement than manual reduction. However, these concepts have never been scientifically evaluated. We compared these 2 methods in a prospective randomized trial. A total of 85 acute ankle rotational fractures combined with syndesmotic injury were randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…This process often utilizes compressive clamping across the syndesmosis, 9 which can malreduce and/or overcompress the syndesmosis. 19 The use of a calibrated syndesmotic reduction clamp in this work resulted in well-controlled load application along specific transsyndesmotic vectors. Under these conditions, it was found that when the medial tine of the clamp was positioned anterior to the midline of the medial tibia, progressively increasing clamp force caused little fibular malalignment relative to the tibia.…”
Section: Discussionmentioning
confidence: 96%
“…This process often utilizes compressive clamping across the syndesmosis, 9 which can malreduce and/or overcompress the syndesmosis. 19 The use of a calibrated syndesmotic reduction clamp in this work resulted in well-controlled load application along specific transsyndesmotic vectors. Under these conditions, it was found that when the medial tine of the clamp was positioned anterior to the midline of the medial tibia, progressively increasing clamp force caused little fibular malalignment relative to the tibia.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, the most common intraoperative reduction technique for injuries of the syndesmotic region is the conventional bone reduction forceps. Nevertheless, prospective studies have shown that the manual reduction technique is comparable 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common reduction method in the operative treatment of unstable syndesmotic injuries is the conventional bone reduction forceps. Nevertheless, prospective studies have shown that the manual reduction technique is comparable 24 . There are no studies on the collinear reduction clamp for unstable ankle injuries, but good reduction results have been demonstrated in other fracture regions such as the acetabulum 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The hook test was defined as positive if >2 mm of lateral fibula movement was observed. 23 In cases where syndesmosis injury was present and the hook test was positive, syndesmosis transfixation was performed at 2 to 3 cm above the ankle joint using a 3.5-mm cortical screw.…”
Section: Methodsmentioning
confidence: 99%